2005
DOI: 10.1111/j.1600-0528.2005.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

The Children's Fear Survey Schedule–Dental Subscale in Japan

Abstract: The results suggest that the CFSS-DS is reliable and valid and operates in Japan as it does in other cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
109
1
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(174 citation statements)
references
References 24 publications
(65 reference statements)
41
109
1
18
Order By: Relevance
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 81%
See 1 more Smart Citation
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 81%
“…U našem istraživanju srednja vrijednost CFSS-DS-a za dječake bila je 19,23+/-6,30, a za djevojčice 22,17+/-10,72, odnosno srednja vrijednost anksioznosti bila je značajno veća kada je riječ o djevojčicama negoli o dječacima (p = 0,006). Naši su rezultati slični onima Tena Berge i suradnika (17), Maje i suradnika (18), Majstorović i suradnika (19) te Nakaija i suradnika (20). Neka istraživanja nisu pokazala značajnu razliku srednjih vrijednosti ankioznosti između dječaka i djevojčica (srednja vrijednost CFSS-DS-a za djevojčice u odnosu prema dječacima; 27,50+/-5,01 i 26,84+/-5,62, tim redom) (21).…”
Section: Raspravaunclassified
“…A previous report has already disclosed similar results (10). A reasonable explanation for this association is that due to cultural issues, girls probably feel more comfortable to express their feelings and confess their fears (16).…”
Section: Discussionsupporting
confidence: 65%
“…The age of the child plays a crucial role in the prevalence of dental fear (3,10). Most studies of the factors affecting dental fear were focused in preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between the FIS and VPT scores was also observed in the study by Buchanan and Niven 6 Our study showed that 8.9% of the children received a "negative and definitely negative" Frankl behavior rating score. Yamada et al 16 reported 8% of the children receiving this score, whereas Nakai et al 23 reported 15%. In our study, 8.9% of the children refused the oral examination and 15.6% rejected fluoride application, which is in agreement with the above articles.…”
Section: Discussionmentioning
confidence: 96%